Accelerating Business Transformation of Enterprises by Leveraging SAP - Banerjee, Debajit (Digital Repository of Theses - SSBM Geneva, 2025)
Ever-transforming IT environment, increasing cloud-based applications triggering enterprises to embrace changes to adopt business transformation to stay market relevant. This transformation poses significant challenges, particularly for enterprises that have been operating complex and cumbersome legacy business systems on-premises for years. Even for those with smoothly running SAP implementations, the shift to private or public cloud environments presents its own set of difficulties. Business transformation involves a series of internal and external changes, which a company undergoes - leveraging digital technologies as per the market demand to a more agile, optimized manner. Enterprises aim to standardize, harmonize, and consolidate various business processes and system landscapes to deliver business value effectively and efficiently – without many disruptions. This paper highlights the challenges faced by enterprises when considering changes to their established legacy or SAP system landscape due to business transformation initiatives. A sincere effort made here also on how enterprise can leverage systematic approach using proposed frameworks smoothen their transformation journey using modern product/technology/service advancement from SAP. Keywords Enterprise, SAP, ERP, Implementation, Technology, Business Transformation